The Relationship of Good Manners with the Learning Creativity of Students in the Field of Islamic Studies - Hamzah Hamzah; Pinta Kemala Sari Hasibuan (International Journal on Social Science, Economics and Art, 2022)
The purpose of this study was to determine the relationship between good manners and the learning creativity of students in the field of Islamic Religious Education at SMA Negeri 3 Teluk Meranti. The relationship between good manners and students' learning creativity is to develop students' creative thinking actively and systematically and to get verbal responses from students so that they can foster learning creativity and new knowledge in the learning process. So that with the existence of good manners in students, they will increase their creativity and become active. However, based on a preliminary study that the author conducted on students of SMAN 3 Teluk Meranti. In daily activities there are still students who do not show their creativity so that students do not play an active role in speaking and some do not dare to express their opinions. The purpose of this study was to determine the relationship between good manners and the learning creativity of students in the field of Islamic Religious Education Studies at SMAN 3 Teluk Meranti. This type of research is correlational, population and sample are 75 students, data collection techniques are questionnaires and documentation, person correlation data analysis techniques. The results of research on the relationship of good manners with learning creativity can be seen from the product moment correlation analysis, meaning that there is a relationship between good manners and the learning creativity of students. And the relationship level is 0.946. The conclusion of this study is that there is a very strong relationship between good manners and student learning creativity in Islamic Religious Education subjects at SMAN 3 Teluk Meranti.